It is given that a , b , c are sides of a triangle Δ A B C and the roots of the equation below.
x 3 − 2 4 x 2 + 1 8 0 x − 4 2 0 = 0 .
If the value of sin A + sin B + sin C = q p , where p , q are coprime positive integers , find p + q − 1 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
No wonder I had difficulties solving...I didn't know Heron's Formula
Btw, this title seems awfully familiar...
Log in to reply
Yep... It resembles the title you used for posting your Vieta problem... :-p
Really a nice solution. I really like your idea of relating the factored form to the standard form of the cubic equation and substituting 12 for x to arrive for the area. Using this, I have posted a solution with some variations. Thanks.
By sine rule, we have: a sin A = b sin B = c sin C = k ⟹ ⎩ ⎪ ⎨ ⎪ ⎧ sin A = k a sin B = k b sin C = k c
⟹ sin A + sin B + sin C ⟹ q p = k ( a + b + c ) = 2 4 k = 2 4 k Vieta’s formula: a + b + c = 2 4
Area of triangle A △ = 2 1 a b sin C = 2 1 a b c k . By Vieta's formula , we have a b c = 4 2 0 ⟹ A △ = 2 1 0 k .
By Heron's formula ,
A △ = s ( s − a ) ( s − b ) ( s − c ) = 1 2 ( 1 2 − a ) ( 1 2 − b ) ( 1 2 − c ) = 1 2 ( 1 2 ) = 1 2 where s = 2 1 ( a + b + c ) and Vieta’s formula: a + b + c = 2 4 Note that: x 3 − 2 4 x 2 + 1 8 0 x − 4 2 0 = ( x − a ) ( x − b ) ( x − c )
⟹ 2 1 0 k = 1 2 ⟹ k = 3 5 2 ⟹ q p = 3 5 4 8 ⟹ p + q − 1 0 = 7 3
Nice solution.
I did a similar solution but yours is much cleaner than mine. I related everything to Sin B instead of k (using the Sine Law) and I also expanded Heron's formula and used Vieta's formula directly. I really like your idea of relating the factored form to the standard form of the cubic eqn. and substituting 12 into x. Beautiful solution.
A Beautiful Solution. I really like your idea of relating the factored form to the standard form of the cubic equation and substituting 12 for x to arrive for the area. Using this, I have posted a solution with some variations. Thanks.
x 3 − 2 4 x 2 + 1 8 0 x − 4 2 0 = 0 . b y V i e t a ′ s f o r m u l a , c y c ∑ a = 2 4 , c y c ∑ a b = 1 8 0 , a b c = 4 2 0 . A f t e r n o r m a l m a n u p u l a t i o n s , w e g e t c y c ∑ a 2 = 2 1 6 , a n d c y c ∑ a 2 b 2 = 1 8 0 2 − 2 ∗ 4 2 0 ∗ 2 4 = 1 2 2 4 0 . U s i n g C o s L a w , S i n A = 1 − C o s 2 A = 2 b c 1 ∗ 4 b 2 c 2 − ( − a 2 + b 2 + c 2 ) 2 . S i n A = 2 a b c a ∗ 4 c y c ∑ a 2 b 2 − { c y c ∑ a 2 } 2 . c y c ∑ S i n A = 2 a b c c y c ∑ a ∗ 4 c y c ∑ a 2 b 2 − { c y c ∑ a 2 } 2 . c y c ∑ S i n A = 2 ∗ 4 2 0 2 4 ∗ 4 ∗ 1 2 2 4 0 − 2 1 6 2 = 2 ∗ 4 2 0 2 4 ∗ 4 8 = 3 5 4 8 = q p . p + q − 1 0 = 7 3 . .
This is how I arrived at the solution. But a straight solution below.
Thanks to @Chew-Seong Cheong and @Rishabh Cool for the method below.
U s i n g V i e t a ′ s F o r m u l a c y c ∑ a = 2 4 , c y c ∑ a b = 1 8 0 , a b c = 4 2 0 . S e m i p e r i m e t e r = s = 2 1 ∗ c y c ∑ a = 1 2 Now using Heron’s formula for finding area:- ∵ f ( x ) = x 3 − 2 4 x 2 + 1 2 0 x − 4 2 0 = ( x − a ) ( x − b ) ( x − c ) ∴ [ A B C ] = s ∗ f ( s ) = 1 2 { f ( 1 2 ) ( 1 2 − a ) ( 1 2 − b ) ( 1 2 − c ) } ∴ [ A B C ] = 1 2 f ( 1 2 ) = 1 2 ⋅ 1 2 = 1 2 S i n A = b c 2 [ A B C ] = a b c 2 a [ A B C ] . c y c ∑ S i n A = c y c ∑ a b c 2 a [ A B C ] 4 2 0 2 ∗ 2 4 ∗ 1 2 = 3 5 4 8 = q p . p + q − 1 0 = 7 3 .
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Vieta's Formula Problem Solving - Intermediate
Calling the expression I ( = cyc ∑ sin A ) and using sine rule, sin A = 2 R a .
I = cyc ∑ 2 R a = 2 R cyc ∑ a = 2 Δ a b c cyc ∑ a
Now using Vieta's formula, cyc ∑ a = 2 4 , a b c = 4 2 0 so that:
I = 3 5 4 Δ
Semi perimeter = s = 2 cyc ∑ a = 1 2 . Now using Heron's formula for finding area:-
Δ = 1 2 { f ( 1 2 ) ( 1 2 − a ) ( 1 2 − b ) ( 1 2 − c ) }
( ∵ f ( x ) = x 3 − 2 4 x 2 + 1 2 0 x − 4 2 0 = ( x − a ) ( x − b ) ( x − c ) )
= 1 2 f ( 1 2 ) = 1 2 ⋅ 1 2 = 1 2
Hence, I = 3 5 4 8 .
4 8 + 3 5 − 1 0 = 7 3